Pyrrovobasine, hybrid alkylated pyrraline monoterpene indole alkaloid pseudodimer discovered using a combination of mass spectral and NMR-based machine learning annotations. Issue 1 (1st October 2021) - Fouotsa, Hugues; Mkounga, Pierre; Lannang, Alain Meli; Vanheuverzwijn, Jérôme; Zhou, Zhiyu; Leblanc, Karine; Rharrabti, Somia; Nkengfack, Augustin Ephrem; Gallard, Jean-François; Fontaine, Véronique; Meyer, Franck; Poupon, Erwan; et al.
Abstract : The MS 2 -guided phytochemical investigation of Voacanga africana stem bark resulted in the isolation of pyrrovobasine, the first pyrraline-containing MIA. Abstract : A new vobasine–tryptamine-based monoterpene indole alkaloid pseudodimer was isolated from the stem bark of Voacanga africana . As a minor constituent occurring in a thoroughly investigated plant, this molecule was targeted based on a molecular networking strategy and a rational MS 2 -guided phytochemical investigation led to its isolation. Its structure was formally established based on HRMS, 1D/2D NMR data, and the application of the tool Small Molecule Accurate Recognition Technology (SMART 2.0). Its absolute configuration was assigned by the exciton chirality method and TD-DFT ECD calculations. Besides featuring an unprecedented intermonomeric linkage in the small group of vobasine/tryptamine hybrids, pyrrovobasine also represents the first pyrraline-containing representative in the whole monoterpene indole alkaloids group. Biosynthetic hypotheses possibly underpinning these structural oddities are proposed here.